(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Technology application during the Green Revolution had been successfully worked to overcome the national food production deficit. However, due to the policy to maintain low food prices, the increase of production failed to improve the actual farmer’s income. The strategy to differentiate agricultural products with premium prices is set through a logo or brand seal on the products, means that the products are explicitly embedded with environment friendly images, safe and sustainable. The suggested logo is “Green Food” indicated that the products come from “green Agriculture”. The Green Agriculture is a modern agricultural practice using a balanced and controlled agrochemical according to certain protocol to guarantee an environment friendly production process and safety consume of the products. Green Agriculture and the Green Food easier to apply compared to that of Good Agriculture Practices. If Indonesia to adopt Green Agriculture and Green Food, a new regulation called “Indonesian Green Agriculture and Green Food Protocol” need to be formulated. For operational reason, the need to adopt Green Agriculture and Green Food should come from the incumbent and influenced government officials. Green Agriculture and Green Food is a branding strategy to increase the bargaining position and the competitive level of Indonesian agricultural products at both domestic and international markets. China has applied Green Agriculture and Green Food since 1990 and in 2008, 6 million of China’s farmers have adopted the practices along with 816 post-harvest processors with annual Green Food total volume amounted to 42 million ton and US 2.32 billion of export value. In Indonesia, Green Food has a high opportunity to get market segment due to the increase awareness on environment quality in addition to higher prices the farmers could enjoy compared to the price of conventional products. Through Green Agriculture and Green Food, the maintenance of environment quality and safety of food consumption will be a collective responsibility of the farmers, processors, traders, and consumers. Green Agriculture and Green Food is the “eco-farming with modern techniques and modern management by modern farmers for modern societies and modern world”.